ANALYSIS OF FLOOD VULNURABILITY AMONG LOWLAND RICE FARMERS IN KOGI STATE - Umar, S.; Halliru, M.; Shuaib, K.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analyzed the flood vulnerability among lowland rice farmers in Kogi State. A multistage sampling technique was employed to select 218 respondents across flood-prone communities. Data were collected using structured questionnaires and analyzed using descriptive statistics and Flood Vulnerability Index (FVI), respectively. The findings revealed that majority (82.6%) of the rice farmers were male, within the mean age of (40.88 years) economically active group, with low educational attainment and a high dependence on farming. The results indicated that majority (87.2% and 70.2%) of the rice farmers were exposed to flood and attested that floods is severe. Also 76.1% of the rice farmers reported that they experience flooding every year and 52.8% attributed the source of flooding to the river in the study area. The FVI results indicated a low level of vulnerability, characterized by high exposure in Kabawa (0.772), Okumi (0.755) and S/Noma (0.728) with sensitivity 0.560, 0.583 and 0.583 respectively, as well as high adaptive capacity. Additionally, farmers adopted coping mechanisms including livelihood diversification, use of early warnings, and reliance on communal and institutional support. The study concludes that lowland rice farmers in study area experience recurrent and severe flooding. It recommends the development of context-specific flood mitigation infrastructure, improved access to agricultural inputs and credit, and strengthened extension services to build resilience and reduce rural poverty.